2019
DOI: 10.18287/2412-6179-2019-43-6-976-982
|View full text |Cite
|
Sign up to set email alerts
|

Properties of nematic LC planar and smoothly-irregular waveguide structures: research in the experiment and using computer modeling

Abstract: Nematic liquid crystal planar and smoothly-irregular waveguide structures were studied experimentally and by the computer modeling. Two types of optical smoothly-irregular waveguide structures promising for application in telecommunications and control systems are studied by numerical simulation: liquid crystal waveguides and thin film solid generalized waveguide Luneburg lens. Study of the behavior of these waveguide structures where liquid crystal layer can be used to control the properties of the entire dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…The results of the numerical modeling showed that the considered twodimensional model with a constant electric field varying within wide limits did not allow us to give a complete explanation of the effect observed in the experiment with 2D LC cell [12,13,15,16], which apparently is conditioned by the pulse-periodic character of the applied electric field [15] and 2D character of the Frederiks's effect [16][17][18]21]. Note that we didn't take into account other possible effects, e.g.…”
Section: Theory and Experiment Results Of Computer Modelingmentioning
confidence: 90%
See 4 more Smart Citations
“…The results of the numerical modeling showed that the considered twodimensional model with a constant electric field varying within wide limits did not allow us to give a complete explanation of the effect observed in the experiment with 2D LC cell [12,13,15,16], which apparently is conditioned by the pulse-periodic character of the applied electric field [15] and 2D character of the Frederiks's effect [16][17][18]21]. Note that we didn't take into account other possible effects, e.g.…”
Section: Theory and Experiment Results Of Computer Modelingmentioning
confidence: 90%
“…If the directions of the field and director in the initial state do not satisfy the condition of the minimum of the free energy at quite a high field which is capable of overcoming the NLC's elastic forces, the director will be reoriented and its new stationary distribution will be established. In our previous paper when carrying out the standard minimization procedure for the free energy of the ensemble of NLC molecules [15] in the external electric field E and not going beyond the qualitative estimation of the final results to simplify the problem's solution, we obtained the second-order partial differential equation [12,15,16,18,21]. Then the numerical solutions of this equation with known boundary conditions were obtained and studied.…”
Section: Theory and Experiment Results Of Computer Modelingmentioning
confidence: 99%
See 3 more Smart Citations